Optimal Placement and Sizing of Distributed Generation Units Using Co-Evolutionary Particle Swarm Optimization Algorithms - Alireza Kaviani-Arani (Institute of Advanced Engineering and Science, 2015)
Today, with the increase of distributed generation sources in power systems, it’s important to optimal location of these sources. Determine the number, location, size and type of distributed generation (DG) on Power Systems, causes the reducing losses and improving reliability of the system. In this paper is used Co-evolutionary particle swarm optimization algorithm (CPSO) to determine the optimal values of the listed parameters. Obtained results through simulations are done in MATLAB software is presented in the form of figure and table in this paper. These tables and figures, show how to changes the system losses and improving reliability by changing parameters such as location, size, number and type of DG. Finally, the results of this method are compared with the results of the Genetic algorithm (GA) method, to determine the performance of each of these methods. DOI: http://dx.doi.org/10.11591/telkomnika.v13i2.7026